2016
DOI: 10.4143/crt.2015.391
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy Alone in cT1-3N0 Non-small Cell Lung Cancer Patients Who Are Unfit for Surgical Resection or Stereotactic Radiation Therapy: Comparison of Risk-Adaptive Dose Schedules

Abstract: PurposeHigh dose definitive radiation therapy (RT) alone is recommended to patients with cT1-3N0 non-small cell lung cancer, who are unfit for surgery or stereotactic RT. This study was conducted to evaluate the clinical outcomes and cost-effectiveness following RT alone using two different modest hypofractionation dose schemes.Materials and MethodsBetween 2001 and 2014, 124 patients underwent RT alone. From 2001 till 2010, 60 Gy in 20 fractions was delivered to 79 patients (group 1). Since 2011, 60 Gy in 20 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Less toxicity was reported in the 15-fraction arm. Cho et al [21] retrospectively reviewed hypofractionated radiotherapy for medically inoperable T1eT3 N0 NSCLC using a risk-adaptive dose schedule (60 Gy in four, 15 or 20 fractions depending on location, size and geometry of the tumour in relation to the oesophagus). In total, 124 patients were included in the study: 72.6% had T1e2 N0 tumours; 65.3% had centrally located disease; 44.1% had performance status 2e3; and 20.2% received 60 Gy/15 fractions.…”
Section: Evidencementioning
confidence: 99%
“…Less toxicity was reported in the 15-fraction arm. Cho et al [21] retrospectively reviewed hypofractionated radiotherapy for medically inoperable T1eT3 N0 NSCLC using a risk-adaptive dose schedule (60 Gy in four, 15 or 20 fractions depending on location, size and geometry of the tumour in relation to the oesophagus). In total, 124 patients were included in the study: 72.6% had T1e2 N0 tumours; 65.3% had centrally located disease; 44.1% had performance status 2e3; and 20.2% received 60 Gy/15 fractions.…”
Section: Evidencementioning
confidence: 99%
“…However, due to the lack of confirmatory level I trial evidence, caution needs to be exercised when using this schedule concurrent with chemotherapy in patients with bulky mediastinal disease. Other options available are 60−72 Gy at 20-24 fx [16]. For those patients with concurrent chemotherapy, RT should be started on day 1 of chemotherapy, so only two cycles will be needed [17].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple older studies [19] showed no survival benefit to PORT but recent data suggest benefit of modern PORT for pN2 patients [20]. PORT in pN2 or incompletely resected stage II and III NSCLC could be reasonably delayed with an imaging re-evaluation before treatment at 2−3 months or treated in 20 fractions (55−60 Gy) [15,16,21]. 5 In NSCLC patients with limited metastases, local consolidative therapy with RT could be either delayed or even omitted since there is no phase III evidence showing a survival benefit in this subset of patients.…”
Section: Suggested Recommendations (mentioning
confidence: 99%
See 1 more Smart Citation
“…The planning target volume or block margin was determined based on the RT modalities: 5 mm for IMRT, stereotactic body radiotherapy (SBRT), and PBT; and 1.0-1.5 cm for three-dimensional conformal radiotherapy (3D-CRT). RT doses were administered in various fractionated schedules based on the treatment conditions, including the estimated risk of esophagitis: 60-70 Gy with 2-2.2 Gy per fraction for concurrent chemoradiotherapy, 50-66 Gy with 2-8 Gy per fraction for RT alone, and 48-60 Gy with 12-15 Gy per fraction for SBRT [3,5,10,11]. Generally, the dose fractionation schedules did not differ between XRT and PBT or between the two centers.…”
Section: Re-irradiationmentioning
confidence: 99%